2019
DOI: 10.1136/fmch-2018-000007
|View full text |Cite
|
Sign up to set email alerts
|

Health services utilisation and responsiveness profiles in Iran: a provincial household study

Abstract: ObjectiveThe aim of this study was to describe health services utilisation and responsiveness in East Azerbaijan province, Iran.DesignA cross-sectional household study as part of a larger research on primary healthcare system.SettingWe carried out the study in East Azerbaijan Province, northwest Iran from July to September 2015.ParticipantsA total of 1318 households were included.ResultsMost of the participating households had social security health insurance. Heart failure or hypertension care, general outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Considering the significance of community participation in safety promotion initiatives and their sustainability, online reporting systems could play a vital role in establishing and maintaining a connection between the community and authorities ( 12 , 13 ). Community reporting systems provide a crowdsourcing platform that gives first-hand data from the public to authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the significance of community participation in safety promotion initiatives and their sustainability, online reporting systems could play a vital role in establishing and maintaining a connection between the community and authorities ( 12 , 13 ). Community reporting systems provide a crowdsourcing platform that gives first-hand data from the public to authorities.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 This is closely related to the health resource services that patients use and the pathological changes caused by changes in trace elements (e.g., melatonin) in their bodies. 5 , 6 Studies in the United States have shown that the death rate from coronary artery disease has dropped sharply over the past four decades, but this favorable trend does not appear to extend to young people, especially young women. Similarly, the hospitalization rate for AMI in young people has not decreased.…”
Section: Introductionmentioning
confidence: 99%